Students' Critical Mathematical Thinking Skills and Character: Experiments for Junior High School Students through Realistic Mathematics Education Culture-Based - Anderson L. Palinussa (Journal on Mathematics Education, 2013)
This paper presents the findings of a quasi-experimental with pre-test-post-test design and control group that aims to assess students' critical mathematical thinking skills and character through realistic mathematics education (RME) culture-based. Subjects of this study were 106 junior high school students from two low and medium schools level in Ambon. The instruments of the study are: students' early math skills test, critical thinking skills mathematical test and perception scale of students' character. Data was analyzed by using t-test and Anova. The study found that: 1) Achievements and enhancement of students' critical mathematical thinking skills who were treated with by realistic mathematics education is better then students' skills were treated by conventional mathematics education. The differences are considered to: a) overall students, b) the level of early math skills, and c) schools' level; 2) Quality of students' character who were treated by realistic mathematics education is better then students' character who were treated by conventional mathematics education The differences are considered to: a) overall students, b) the level of early math skills, and c) schools' level Keywords: Critical Thinking, Students' Character, Realistic Mathematics Education Culture-Based